2002
DOI: 10.1034/j.1399-6576.2003.470102.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic deficits and arachnoiditis following neuroaxial anesthesia

Abstract: Of late, regional anesthesia has enjoyed unprecedented popularity; this increase in cases has brought a higher frequency of instances of neurological deficit and arachnoiditis that may appear as transient nerve root irritation, cauda equina, and conus medullaris syndromes, and later as radiculitis, clumped nerve roots, fibrosis, scarring dural sac deformities, pachymeningitis, pseudomeningocele, and syringomyelia, etc., all associated with arachnoiditis. Arachnoiditis may be caused by infections, myelograms (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 98 publications
0
39
0
5
Order By: Relevance
“…Local anaesthetics themselves have been proposed as a cause of adhesive arachnoiditis [1,17], although this suggestion is controversial. Laboratory studies have demonstrated dose-dependent damage to neural elements exposed to supra-clinical concentrations of local anaesthetic [33].…”
Section: Precipitating Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Local anaesthetics themselves have been proposed as a cause of adhesive arachnoiditis [1,17], although this suggestion is controversial. Laboratory studies have demonstrated dose-dependent damage to neural elements exposed to supra-clinical concentrations of local anaesthetic [33].…”
Section: Precipitating Agentsmentioning
confidence: 99%
“…Obstetric procedures predominate and development of symptoms severe enough to warrant neurosurgical referral is usually in the order of days to weeks following the anaesthetic. The temporal relationship between the neuraxial anaesthetic and the development of adhesive arachnoiditis is compelling in all cases, but the proposed mechanisms of initial injury remain speculative and controversial [1,5,17]. They include an inflammatory response to blood in the subarachnoid space, the action of the local anaesthetics themselves and accidental contamination of the injectate.…”
Section: Precipitating Agentsmentioning
confidence: 99%
See 3 more Smart Citations